PENGARUH PENGGUNAAN AIR KELAPA HYBRIDA (Cocos nucifera) DENGAN DOSIS YANG BERBEDA TERHADAP MASKULINISASI LARVA IKAN GUPPY (Poecilia reticulata) - Irvandu Putra Perdana; Iskandar Johan; Muhammad Hasby (DINAMIKA PERTANIAN, 2022)
The purpose of this study is to determine the effectiveness of using young coconut water as an alternative material for masculinizing guppy fish through different immersion times on guppy fish larvae. This research was carried out for 50 days starting from October 25 to December 14, 2020, at the Fish Seed Center (BBI) of the Islamic University of Riau Pekanbaru. The method in this study used a completely randomized design (CRD) method with five treatments and three replications. The treatments used were soaking time of 8 hours with doses using hybrid coconut water, namely: P0: without using coconut water, P1: 50 ml, P2: 100 ml, P3: 150 ml, and P4: 200 ml. The experimental treatments were carried out on guppy fish (Poecilia reticulata) larvae. The containers used were 15 units of jars with a capacity of 10 liters which was filled with treatment media with a stocking density of 15 fish/jar. Based on the results, it was found that the highest male sex direction in guppies was in treatment P4 with a dose of 200 ml with a soaking time of 8 hours with the number of males produced at 94% and the lowest was in treatment P0 without using a dose of young coconut water which was only produced 37% males with a very low survival rate. Analysis of variance showed that F count (2.59) < F table 0.05 (3.48) at the 95% accuracy level, where different doses of masculinization of guppies (Poecilia reticulata) were not significantly different. Climatic data in the form of temperature was 28-32 0C, pH 5-7 and DO 5,7-8,20 mg/l.